Extracting invariants based on coordinate transformations - Tao, Ngo Quoc (Journal of Computer Science and Cybernetics, 2016)
This paper deals with some methods extracting invariants for the translation, rotation and scaling and finding invariants which are depended on statistic invariants. It collates them with the Fourier transform. For discrete point set we can use the polar coordinate to  construct SCC (star contour code) and give match algorithm for SCC.